Factors possibly inhibiting growth of herbaceous plants in the understories of Eucalyptus cinerea - Tshivhandekano, Thivhulawi Robert (Department of Biological Sciences, 2017)
Eucalyptus baxteri has been reported to produce a zone of suppression beneath its canopy when growing in coastal heath (De Moral, Willis and Ashton 1978). In their studies, investigations of ecophysiological parameters of soil water potential, soil nutrient levels and shading failed to account for suppression of understorey species. Their studies have shown that suppression of herbaceous layer species beneath the canopy of E. baxteri appear to be of an allelopathic rather than a competitive nature. Although the suppression of growth of herbaceous layer species under the understoreys of so many different Eucalyptus species has been attributed to allelochemicals produced by these trees, it is possible that suppression is due to other factors rather than toxicity of soil beneath Eucalyptus stands. The effects of plant competition for light, water and nutrients cannot totally be ignored when factors affecting the growth of herbaceous layer species under Eucalyptus understories are considered. For example, Lamont (1985) demonstrated that allelochemicals produced by leaves of Eucalyptus wandoo were not responsible for the suppression of herbaceous plants in the understorey of this plant species. From his study, it was found that competition for water at depth between the extensive lateral root system of E. wandoo trees and roots of adult shrubs was a more likely explanation for genesis of a suppression zone and location of its boundary. Therefore, to determine the meaning of Eucalyptus undergrowth effects, careful chemical detective work may be necessary. One need to establish first that the effect is in fact chemical and not one of competition between plants for light, water or nutrients. If it is possible, one must show that under natural conditions the quantitative relations of the chemical agents identified as they occur in the soil are adequate to produce the observed degree of inhibition of other plants which can be difficult to prove (De Moral et al. 1970). In Cape Town (South Africa), below Table Mountain, there is a bare area that resulted from the removal of an Eucalyptus cinerea stand. The strange thing about this bare area, is that from the time the Eucalyptus were clear-felled, it has been very difficult for plant species to regenerate in that bare area. The bare area has been apparent for about 5 years. The main objective of this study was to try and isolate these factors which might have been responsible for the suppression of growth under Eucalyptus stands, and their subsequent effect on regrowth after clear-felling. Therefore, this study was undertaken to test the following hypotheses. (1) Allelochemical Hypothesis. Since the genus Eucalyptus has been shown to produce several volatile terpenes, of which several have been shown to be toxic to seed germination and seedling growth, Eucalyptus trees might have been produced allelochemicals that were leached into the soil. These allelochemicals might be the ones that are responsible for inhibiting regeneration of plant species, even after the Eucalyptus cinerea trees were removed. (2) Topsoil Erosion Hypothesis. Since the understories of Eucalyptus were not rich in vegetation cover, the top soil, which is rich in nutrients and good for seedling establishment, was eroded down the slope. As a result, only the sub-soil was left. Plants were therefore unable to establish themselves in soils of such poor nutritional status with such low seed banks. (3) Soil Nutrient Depletion Hypothesis. Eucalyptus might have depleted most of the soil nutrients before they were clear-felled. Therefore, even after their removal, the nutrient status of the soil was poor in such a manner that very few plant species could establish themselves.